Is renewable energy storage sustainable? A review - Aleksandar Anastasovski (Green Technologies and Sustainability)
Transformation of energy supply systems into green intensifies the use of renewable energy sources. Renewables cannot continuously supply energy. Therefore, energy storage systems are very important in the whole system of generation and distribution. Anyway, energy storage systems have many issues in terms of sustainability. This paper classified energy storage and analyzed issues in their sustainability solutions. In addition, it determines the key performance indicators that define the sustainability of energy storage systems. This analysis determined many sustainability problems presented by the information for each key performance indicator. The least negative impact is shown for the performance of mechanical energy storage and sensible/latent heat storage. The production of green hydrogen, green ammonia and biogas showed some negative impact. The worst sustainability is related to energy storage technologies or electrochemical energy storage technologies.